Acute necrotic hepatotoxicity caused by Lantana camara L. ingestion in dairy cattle - Silva,Emanoelly M.S. (2021)
ABSTRACT: This study describes an outbreak of acute necrotic hepatopathy associated with spontaneous poisoning by Lantana camara L. in dairy cattle. A herd of 15 cows and heifers was introduced into a native pasture with limited food supply, and, sixteen days later, eight animals had spontaneous nasal hemorrhage, fever, lethargy, jaundice, and dry, dark stools with mucus and blood. The clinical course varied from two to five days. In the pasture where the cattle were kept, abundant adult specimens of L. camara L. with evident signs of consumption were observed. In total, seven cattle died and necropsy was performed in three of them. All animals had moderate jaundice, hemorrhage in the subcutaneous tissue and on the surface of different organs. The liver was slightly enlarged, with orange discoloration and enhanced lobular pattern. Histologically, multifocal areas of coagulative necrosis of hepatocytes in the centrilobular area, occasionally extending to the midzonal area, were observed, as well as marked hepatocellular degeneration and prominent cholestasis. The current study suggests that L. camara L. poisoning should be considered a differential diagnosis of acute and necrotic hepatotoxicity in cattle, despite the absence of photosensitization.